Host Plant Volatile Lures Attract Apanteles polychrosidis (Hymenoptera: Braconidae) to Ash Trees Infested With Caloptilia fraxinella (Lepidoptera: Gracillariidae) - McPike, Sarah M.; Evenden, Maya L. (Frontiers in Ecology and Evolution, 2021)
Caloptilia fraxinella Ely (Lepidoptera: Gracillariidae), the ash leaf-cone roller, is an aesthetic pest of horticultural ash trees (Oleaceae, Genus Fraxinus) in prairie communities across Canada. Because pesticide use is undesirable in urban centers, biological control of C. fraxinella is a preferred approach. The native parasitoid wasp, Apanteles polychrosidis Vierek (Hymenoptera: Braconidae), has shifted hosts and is the primary parasitoid of C. fraxinella in Edmonton, Alberta, Canada, and has potential as a biological control agent. Here, in an effort to increase parasitism of C. fraxinella, lures releasing methyl salicylate (MeSA) and two green leaf volatiles (GLVs), ((Z)-3-hexenol, and (Z)-3-hexenyl-acetate), at both low and high release rates, were tested to enhance attraction and retention of A. polychrosidis in infested ash trees. Attraction of A. polychrosidis to baited trees was measured by capture on yellow sticky cards positioned in the tree canopy, and wasp activity was assessed by the parasitism rate of C. fraxinella. More male and female A. polychrosidis were captured on yellow sticky traps positioned in trees baited with the low dose of both MeSA+GLVs than to unbaited, infested ash trees. The increased attraction of wasps did not correlate with an increase in parasitism of C. fraxinella. The high release rate lures did not enhance attraction of A. polychrosidis to infested ash trees. Parasitism rate, however, was negatively correlated with host density in both field experiments. There was no evidence of close-range attraction to lures in an olfactometer assay. Synthetic HIPVs attract A. polychrosidis to ash trees infested with C. fraxinella, but the effect of wasp attraction on parasitism rate requires further research if HIPVs are to be used to enhance biological control in this system.